A General Equilibrium Analysis of Personal Bankruptcy Law. (29th October 2015) - von Lilienfeld‐Toal, Ulf; Mookherjee, Dilip
Abstract : We analyse an economy where principals and agents match and contract subject to moral hazard. Bankruptcy law defines the limited liability constraint in these contracts. We analyse Walrasian allocations to generate the following predictions: (i) weakening bankruptcy law causes redistribution of debt and welfare from poor agents and principals to rich agents; (ii) exemption limits Pareto‐dominate other bankruptcy laws if project size is fixed; (iii) means‐testing (as in recent US personal bankruptcy law) that is ex post pro‐poor in intent makes the poor worse off ex ante .